2004
DOI: 10.1080/08039480410006296
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and lifetime treatment experiences in psychotic patients with and without substance abuse

Abstract: The main objective of this study was to compare symptom load and lifetime treatment experiences between psychotic patients with substance abuse problems and psychotic patients without substance abuse problems. This is a cross-sectional study of 48 patients (26 inpatients and 22 outpatients) in a clinic for early intervention in psychosis. Patients' were grouped into two categories based on whether they had a substance abuse problem or not. Twenty-one (43.8%) had a substance abuse problem and 27 (56.2%) had not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Although some studies showed no significant difference between schizophrenia patients with substance use and non-use [53], most studies have found that comorbid substance use disorder in schizophrenia is associated with lower and less severe negative symptoms [23,24,46,54]. However, significantly increased severity of depression [52,55] manic [52] and anxiety [53] scores were also found in this sub set of patients. Women were found to have greater depression than men [35].…”
Section: Negative Symptomsmentioning
confidence: 61%
See 1 more Smart Citation
“…Although some studies showed no significant difference between schizophrenia patients with substance use and non-use [53], most studies have found that comorbid substance use disorder in schizophrenia is associated with lower and less severe negative symptoms [23,24,46,54]. However, significantly increased severity of depression [52,55] manic [52] and anxiety [53] scores were also found in this sub set of patients. Women were found to have greater depression than men [35].…”
Section: Negative Symptomsmentioning
confidence: 61%
“…There is fair bit of heterogeneity in the findings on positive symptoms. While several studies show a significantly increased severity of positive symptoms [23,24,26,31,46,52] in schizophrenia patients with substance use disorder, some studies have found that these patients have significantly lower positive symptoms [53] and some have shown a lack of significant difference between schizophrenia patients with substance use and non-use [27,54]. This heterogeneity may be explained by variations in the onset of substance use and psychotic episode.…”
Section: Positive Symptomsmentioning
confidence: 99%
“…In summary, these studies find that current substance use disorders are highly prevalent (commonly 40 -50%) and have adverse clinical implications, such as poorer outcome, higher rates of admission and shorter length of hospital stay (73,77,79). There are, however, many methodological differences between these studies, with regard to study population, sample size and definition and measurement of substance use disorders (Table A1).…”
Section: Acute Psychiatric Admissionsmentioning
confidence: 99%
“…2002). Furthermore, a substantial number of patients in general psychiatric health care have substance addiction in addition to other psychiatric diagnoses (Möller & Linaker 2004). Because the majority of these patients share problems, and thus several similar treatment needs, it is possible that perceptions of treatment and recovery among inpatients in psychiatric health care and substance addiction treatment have resemblances.…”
Section: Introductionmentioning
confidence: 99%